Liberdade de inovar como vetor do desenvolvimento socieconômico: construção de uma teoria realista para a gestão do risco da proteção ao segredo empresarial frente a jurisprudência do TST entre 2015 e 2023 - Marques, Juliana Coelho Tavares (2024)
The thesis deals with the importance of the right to innovate in Brazil and how it can be impacted by judicial decisions, especially those of the Labor Courts, that relate to issues inherent to trade secrets, notably through confidentiality and non-competition clauses. The phenomenon is analyzed from the theoretical perspective of American legal realism, which is appropriate for examining the problem, since it highlights the role of the courts in the construction and effectiveness of rights. Certainly, the arguments given to the issue by the judges is of fundamental importance and must be considered by anyone who ventures into the entrepreneurial world, which highlights the importance of studying and building an interpretative parameter that takes into account the resulting risk, shaping the treatment of information that will be used in the workplace. The research problem thus emerges: how is it possible, from the discourse evidenced by the decisions of the Brazilian Superior Labor Court specific to matters of confidentiality and non-competition, to extract elements for the construction of a risk assessment matrix aimed at protecting trade secrets? The chosen hypothesis admits such a possibility and, not only that, it demarcates spaces for the construction of the tool, a risk matrix, which is summarized at the end of the work, which is the main objective of the research. The research is exploratory and propositional in nature, based on a Shumpeterian theoretical framework in the context of information capitalism, as proposed by Manuel Castells. In addition to the interpretation of legal and doctrinal texts, it uses a selection of judgments from the Superior Labor Courts, which form a body of research subjected to the qualitative method of discourse analysis, which was processed using NVivo software, version 14, based on specific reference codes for assembling the risk matrix. Divided into five parts, which address issues related to the role of innovation in capitalist society, national public policy for innovation and the regulatory framework related to the matter, trade secrets and its legal protection and corporate risk management, the study forms the theoretical and empirical framework for satisfying the main objective of the research. This leads to the proposal of a risk matrix, designed to guide appropriate conduct in the treatment of professionals involved in the intellectual process of national companies. The aim is twofold, not just descriptive, but prescriptive, pointing out alternatives for validly preserving the right to innovation in the context of the sustainable economic development that the country must implement.